Pembangunan Website dan Sarana Podcast UMKM Kampung Digital Sentra Kreasi Desa Pameungpeuk - Arry Widodo; Retno Setyorini; Kristina Sisilia; Robbi Hendriyanto; Sri Widaningsih; Rixard George Dillak; Pramitha Aulia; Maulana Rezi Ramadhan; Muhamad Yusuf Ramadhan (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2023)
Podcast content is increasingly being consumed by people in the world. As many as 32% of Indonesian internet users admit that they have listened to podcasts in the past week. Podcasts have become popular among young people in recent years, after platforms such as Spotify made it possible to explore digital content. Business and education topics are included in the top five podcast topic choices, as many as 67% of the 2,500 respondents in Indonesia are familiar with podcasts, and some of them are even loyal listeners. The UMKM Community in the Digital Sentra Kreasi Village is a place where Micro, Small and Medium Enterprises (MSMEs) in Pameungpeuk District and its surroundings gather. This community embraces business people with a variety of products produced. Seeing the potential of Podcasts as a place with quite a large number of listeners in Indonesia, to be used as education and marketing for MSMEs. The MSMEs Community of Kampung Digital Sentra Kreasi intends to build an MSMEs Podcast in collaboration with Telkom University's Ko+Lab and is planned to be held every month.